Correction: What interventions are effective to prevent or respond to female genital mutilation? A review of existing evidence from 2008-2020. - Dennis Juma Matanda; Nina Van Eekert; Melanie Croce-Galis; Jill Gay; Maria Johanna Middelburg; Karen Hardee (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0001855.].